Unpacking Challenges and Reinforcing Evaluations in Bilateral and Multilateral Development Organizations in Egypt - elghonemy, fatema (AUC Knowledge Fountain, 2024)
The research examines evaluations conducted in bilateral and multilateral development organizations considering programs that are funded by governments or international organizations. The Egyptian Government partners with development partners to receive technical assistance in various fields, such as industrial development, technical education, environmental protection, health improvement and refugees’ empowerment. The thesis explores the interlinkage between the development goals and the results framework to achieve sustainable development goals (SDGs). It then goes on to examine the evolution of the function of evaluation and its historical development into becoming a standalone field that serves the decision making, extension and expansion of interventions. As the frequency of international development interventions increases, so does the need to ensure that they are effective, efficient, impactful, sustainable, relevant and coherent - in accordance with what is known as OECD - DAC Criteria Framework to ensure aid effectiveness - and this can be accomplished through evaluations. The thesis used qualitative methodology by conducting 19 KIIs with practitioners, researchers, agencies’ staff members and decision makers as well as government officials. It is important to understand that evaluating development partnership projects in Egypt has its own challenges that hinder the betterment of international development interventions. Understanding the significance of evaluations for projects is the main objective of the thesis as well as highlighting the missed opportunities of not conducting comprehensive evaluations. The findings showed the difference between tick-the-box evaluations and rigorous evaluations while keeping in mind the different factors that should be considered in order to call an evaluation “strong” and “comprehensive”. It sheds light on the different stakeholders and their varying objectives while exploring the possible ways of integrating them into an evaluation participatory approach to maximize evaluation utilization. The recommendations generated by the thesis tackle each challenge by calling for a unified dictionary for staff working in evaluation in Egypt, strengthening ownership for public partners, using multi-layer and independent evaluation institutions and developing capabilities of evaluation stakeholders.